2018
DOI: 10.1111/jdv.14988
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and dermoscopic characteristics of congenital melanocytic naevi

Abstract: Given that there is much controversy on the management and accurate classification of CN, our findings may provide useful information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
(81 reference statements)
0
8
1
2
Order By: Relevance
“…Melanoma specific dermatoscopic features can be seen in melanomas arising on small/medium‐sized CMN. However, changes in dermatoscopic findings may not be always a sign of malignancy because CMN can grow over time and may present with atypical dermatoscopic features 73 …”
Section: Approach To Congenital Melanocytic Naevimentioning
confidence: 99%
See 1 more Smart Citation
“…Melanoma specific dermatoscopic features can be seen in melanomas arising on small/medium‐sized CMN. However, changes in dermatoscopic findings may not be always a sign of malignancy because CMN can grow over time and may present with atypical dermatoscopic features 73 …”
Section: Approach To Congenital Melanocytic Naevimentioning
confidence: 99%
“…However, changes in dermatoscopic findings may not be always a sign of malignancy because CMN can grow over time and may present with atypical dermatoscopic features. 73 Dermatoscopic evaluation of CMN commonly shows globular, reticular-globular, reticular, and homogenous pattern in different age groups. Globular pattern is seen in the first 2 decades, whereas reticular pattern is seen after 3rd and 4th decades.…”
Section: Approach To Congenital Melanocytic Naevimentioning
confidence: 99%
“…An observational study of 77 patients demonstrated that reticular patterns in CMN are more commonly seen in patients aged 12 years or older. In addition, 40% of reticulated patterns were seen on the extremities or head and neck 40‐42 …”
Section: Congenital Melanocytic Nevimentioning
confidence: 99%
“…Physicians planning to use dermoscopy should be familiar with the dermoscopic characteristics of CMN in order to avoid unnecessary excisions of seemingly suspicious lesions (e.g., atypical pigment network in CMN of the extremities) . Standardized photo documentation facilitates the assessment of changing or newly emerging skin lesions over time, especially if different investigators are involved.…”
Section: Multidisciplinary Approachmentioning
confidence: 99%